Utilization of rice and mungbean in longanisa - Magat, Emily L.
Mixtures of mungbean and rice flour were used to partially replace meat in longaniza. Mungbean was used either as mashed, as sprouts or as flour mixed with rice flour in the ratio 3:7. The mixtures were used in the product at levels of 30%, 40% and 50%. Twenty-four consumer panelists evaluated the effects if the type of preparation of mungbean used and the extent of substitution on overall appearance, flavor, texture and general acceptability of the products using nine-poiny Hedonic scales. Samples that obtained consumer acceptance ratings of 5.0 or greater were considered acceptable. Results indicated that pork longanisa that was acceptable to consumers may be produced using mungbean-rice mixtures. Mixtures of boiled mungbean and rice flour may be used up to 50% level of substitution while mungbean sprouts or mungbean flour mixed with rice flour may be used only up to a maximum of 30% level of substitution.